An Update on Virtopsy- A Modern Forensic Investigation Tool - Ahmad, Mushtaq; Rahman, Md Zubaidur; Rahman, Farial Naima (KYAMC Journal, 2021)
Virtopsy is a virtual alternative to a traditional autopsy, conducted with scanning and imaging technology. In developed countries Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are now being evaluated as complementary means for determination of cause of death. This paper explores the latest development and implication of virtopsy from ethical, clinical and technical point of view. Published literature in different journals with strict inclusion and exclusion criteria were extensively reviewed through use of general and Meta search engines to elucidate the applications and implications of virtual autopsy. The modern high-resolution imaging has been used as a well described aid in the setting of post-mortem investigations. Virtopsy introduces a new era in autopsy examination. It utilizes the technological innovation of modern imaging system to obtain best results and three Dimensional (3D) images of the body in multiple plains without mutilation of the human body. Now a days virtopsy is very much acceptable procedure to the forensic society. In western worlds virtopsy is likely to replace conventional autopsies in future. We can also try to implement this modern system in our country. KYAMC Journal.2021;12(1): 48-52